The relationship between rate-dependent metrics in the isomeric squat and isometric mid-thigh pull - Geneau, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Isometric strength assessments have become a popular means of assessing maximal and rate-dependent strength in athletes. The most common tests of multi-joint isomeric strength include the isometric squat and the isometric mid-thigh pull (IMTP). To date, only a single study has evaluated whether there is a difference between the measures of rate-dependent metrics between these two conditions [1]. It is important to also understand the associations between these metrics to determine if the tests assess similar or different qualities. Thus, the purpose of this study was to assess the association between peak and rate-dependent metrics of the isometric squat and IMTP in semi-professional athletes. We hypothesised that there would be strong associations between the peak and rate-dependent metrics between tests. METHODS: Twenty-six male (BM=79.5±8.9 kg) and 27 female (BM=65.7±8.3 kg) athletes from an elite junior Australian rules football (17-19 years of age) league performed trials of the isometric squat and IMTP with instructions to push/pull as fast and as hard as possible. Seven metrics were derived from each test: net peak force [N], net force at 100ms, 150ms, and 200ms [N], and net force/net peak force at 100ms, 150ms, and 200ms [%]. The trial with the highest peak force was used for analysis. RESULTS: There were weak correlations between the metrics of the two isometric tasks (r = 0.22-0.42). CONCLUSION: The present study determined that there were weak associations between rate-dependent metrics of the IMTP and isometric squat. These findings suggest that the two tests may measure different qualities in junior-level athletes. It is recommended that practitioners approach the interpretation of values across isometric tests independently, as they may contain unique information.